2017
DOI: 10.3389/fimmu.2017.00580
|View full text |Cite
|
Sign up to set email alerts
|

Pathophysiology of CD4+ T-Cell Depletion in HIV-1 and HIV-2 Infections

Abstract: The hall mark of human immunodeficiency virus (HIV) infection is a gradual loss of CD4+ T-cells and imbalance in CD4+ T-cell homeostasis, with progressive impairment of immunity that leads ultimately to death. HIV infection in humans is caused by two related yet distinct viruses: HIV-1 and HIV-2. HIV-2 is typically less virulent than HIV-1 and permits the host to mount a more effective and sustained T-cell immunity. Although both infections manifest the same clinical spectrum, the much lower rate of CD4+ T-cel… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
156
0
3

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 208 publications
(160 citation statements)
references
References 81 publications
(98 reference statements)
1
156
0
3
Order By: Relevance
“…Association neither positive nor negative was found between frailty and naïve or memory subsets. One of the strongest correlates for CD4 + T cell decline in HIV-1 infection is the increased frequency of CD4 M T cells and a corresponding deficit of CD4 N T cells [38]. The Frail group exhibited a decreased frequency of CD4 M cells (27.63 vs. 32.88) and an increase in CD4 N (25.11 vs. 20.05) compared to the non-frail group, but these results were not statistically significant (Fig 1a and 1b).…”
Section: Levels Of Cd4 and Cd8 T Cells In Frail Individualsmentioning
confidence: 99%
“…Association neither positive nor negative was found between frailty and naïve or memory subsets. One of the strongest correlates for CD4 + T cell decline in HIV-1 infection is the increased frequency of CD4 M T cells and a corresponding deficit of CD4 N T cells [38]. The Frail group exhibited a decreased frequency of CD4 M cells (27.63 vs. 32.88) and an increase in CD4 N (25.11 vs. 20.05) compared to the non-frail group, but these results were not statistically significant (Fig 1a and 1b).…”
Section: Levels Of Cd4 and Cd8 T Cells In Frail Individualsmentioning
confidence: 99%
“…Human immunodeficiency virus damages the immune system because it targets CD4 + Tlymphocyte cells. As an infected CD4 + cell multiplies, fewer HIV-free working CD4 + cells become available, eventually decreasing the concentration of these cells in the blood (CD4 + count) (6). Consequently, patients become susceptible to a wide range of opportunistic infections, especially if they are not receiving cART.…”
Section: Introductionmentioning
confidence: 99%
“…It has been previously reported that the main difference in lymphoid phenotypes observed in HIV-infected patients is a reduction by 40% in the CD4+ T helper population and a 45% increase in the CD8+ cytotoxic T-cell population [10]. However, despite decades of experimental research, the complete mechanism of CD4+ T depletion in HIV infection still remains to be explained [11].…”
Section: Discussionmentioning
confidence: 99%
“…We are not able to con rm these data in our patients because they have not been evaluated using antibodies directed against the Treg cell population or their subgroups, namely the naïve-resting cells (CD45RA+) and the memory-activated cells (CD45RA−). In both virus infections, the exact reason of the reduction in the lymphocyte numbers in the blood is not clearly de ned yet and many hypotheses have been proposed [11,16]. In particular, it is not clear whether the reduction in the serum levels of T cells is due to an imbalance between production of T-cells and increased apoptosis of CD4+ T cells by viral attack the so-called of "accelerated destruction" hypothesis.…”
Section: Discussionmentioning
confidence: 99%